A Psycholinguistic Analysis of Students’ Speaking Difficulties in English as a Foreign Language Classroom - Harahap, Gairah Rizki; Wahyuni, Dela; Sarahseti, Dian Fanny; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study explores the psycholinguistic factors that contribute to students’ speaking difficulties in English as a Foreign Language (EFL) classrooms. As speaking is a productive skill that requires rapid mental processing, many learners struggle to produce fluent and accurate speech due to cognitive, affective, and linguistic constraints. This research aims to identify how elements such as working memory limitations, lexical retrieval challenges, anxiety, low self-confidence, and insufficient language exposure influence students’ oral performance. Using a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews, and speaking-task analyses involving EFL learners at the tertiary level. The findings reveal that students frequently face difficulties retrieving vocabulary, organizing ideas quickly, and maintaining fluency under time pressure. Psychological barriers such as fear of making mistakes, negative self-perception, and social anxiety also significantly hinder their willingness to speak. Moreover, limited practice opportunities and inadequate classroom interaction further reduce students’ communicative competence. This study underscores the need for pedagogical strategies that address both cognitive and emotional aspects of language learning. Enhancing supportive environments, providing structured speaking tasks, and integrating psycholinguistically informed techniques can help learners improve fluency, accuracy, and overall speaking performance in EFL classrooms.